"Assessment of RIFLE and AKIN criteria to define acute renal dysfunction for HIPEC procedures for ovarian and non ovarian peritoneal malignances". Issue 6 (June 2016) - Arjona-Sánchez, A.; Cadenas-Febres, A.; Cabrera-Bermon, J.; Muñoz-Casares, F.C.; Casado-Adam, A.; Sánchez-Hidalgo, J.M.; López-Andreu, M.; Briceño-Delgado, J.; Rufián-Peña, S.
Abstract: Background: The acute renal dysfunction (ARD) is a common complication in cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC). Our aim is evaluate the ARD post-HIPEC procedures using the RIFLE and AKIN criteria. Evaluate the risk factors and analyze ARD's impact on postoperative course. Methods: From 2011 to 2014, in a retrospective way using a prospective database were operated by HIPEC procedure. The ARD was analyzed by RIFLE and AKIN criteria. The perioperative features were analyzed and a multivariate analysis was performed to define the risk factors to develop the ARD. Results: 141 patients were treated and analyzed. The ARD was detected in 30.5% (Injury 18.4% and Failure 12.1%) when RIFLE criteria were applied. The multivariate analysis detected that decrease of pH during HIPEC [OR = 29.39 (5.09–169.76)], PCI [OR = 1.07 (1.01–1.15)] and ureteral catheters [OR = 12.71 (1.44–111.85)] were associated to the development of acute renal injury (ARI) post-HIPEC. Decrease of Na during HIPEC [OR = 1.15 (1.01–1.30)], intraoperative inotrope use [OR = 3.83 (1.12–13.09)] and PCI [OR = 1.06 (1.0–1.14)] were associated to acute renal failure (ARF) post-HIPEC. The ARD was related to a higher length of stay hospital (17.2 ± 11 vs. 13.8 ± 8 days) (p = 0.05) but no impact in early survival was observed in ARD group. Conclusions: The widespread use of RIFLE criteria for ARD would have major benefits in terms of accurately diagnosing patients undergone HIPEC procedures. The ARD has a detrimental impact in length of stay hospital. The knowledge of risk factors helps us to prevent the ARD post-HIPEC by means of an aggressive and multidisciplinary perioperative management.